THE INFLUENCE OF WORK ENVIRONMENT, FINANCIAL REWARD, AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE (CASE STUDY: AT PT. BANK NEGARA INDONESIA BRANCH OFFICE MANADO) - Wua, Injilia Wulan Gratia (Jurnal Berkala Ilmiah Efisiensi, 2015)
ABSTRACT Â  Human resource issues are still the main focus for the company to be able to survive in the era of globalization. Human resources have a major role in every activity of the company. Although the company has been supported by the infrastructure and natural resources, but without the quality support of human resources, the company activities will not be able to compete properly. The study aim to find out the influence of work environment, financial reward, and organizational culture on employee performance at PT.Bank Negara Indonesia (BNI), Manado. This research is causal type of research and used quantitative method. 60 employees PT. BNI Manado had surveyed as respondents. The result shows that work environment, financial reward, and organizational culture have significant positive influence on employee performance. This company should create a good working environment and good organizational culture as well as provide a bonus to the employees. Â  Keywords: employee performance, work environment, financial reward, organizational culture